Oxide ceramic matrix composite materials for aero-engine applications: a literature review - Karadimas, Georgios; Salonitis, Konstantinos; Georgarakis, Konstantinos (IOS, 2021)
The development of aircraft gas turbine engines has extensively been required for the development of advanced materials. This complex development process is however justified by the system-level benefits in terms of reduced weight, higher temperature capability, and/or reduced cooling, each of which increases efficiency. This is where high-temperature ceramics have made considerable progress and ceramic matrix composites (CMCs) are in the foreground. CMCs are classified into non-oxide and oxide-based ones. Both families have material types that have a high potential for use in high-temperature propulsion applications. Typical oxide-based ones are based on an oxide fiber and oxide matrix (Ox-Ox). Some of the most common oxide subcategories, are alumina, beryllia, ceria, and zirconia ceramics. Such matrix composites are used for example in combustion liners of gas turbine engines and exhaust nozzles. However, until now a thorough study on the available oxide-based CMCs for such applications has not been presented. This paper focus on assessing a literature survey of the available oxide ceramic matrix composite materials in terms of mechanical and thermal properties.
Keywords: Material classification; Oxide-CMC; CMC